Endangered animals of the sea - Rice, William B. (William Benjamin), 1961- (Huntington Beach, CA : Teacher Created Materials, 2013)
Introduces readers to endangered animals that live in the sea.
"Based on writing from Time For Kids"--T.p. verso.
"TCM 15935"-Back cover.
Includes bibliographical references (p. 62-63) and index.
5.5
3-6.
3-6
Keywords: Endangered species -- Juvenile literature; Marine animals -- Juvenile literature; Endangered species; Marine animals; Endangered species; Marine animals